2017
DOI: 10.1103/physrevb.95.140505
|View full text |Cite
|
Sign up to set email alerts
|

Signature of multigap nodeless superconductivity in CaKFe4As4

Abstract: A newly discovered family of high-Tc Fe-based superconductors, AeAFe4As4 (Ae = Ca, Sr, Eu and A = K, Rb, Cs), offers further opportunities to understand unconventional superconductivity in these materials. In this paper, we report on the superconducting and magnetic properties of CaKFe4As4, studied using muon spectroscopy. Zero field muon-spin-relaxation studies carried out on the CaKFe4As4 superconductor do not show any detectable magnetic anomaly at Tc or below, implying that time-reversal-symmetry is preser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
13
40
0
Order By: Relevance
“…22,23) This multiband nature implies multi-gap superconductivity in CaKFe 4 As 4 . Two superconducting gaps which are nodeless and isotropic were, indeed, observed by scanning tunneling microscopy, 20) optical conductivity, 24) penetration depth, 21) muon spin rota- * k iida@cross.or.jp tion, 18) and 75 As nuclear magnetic resonance (NMR) 25) measurements. The largest superconducting gaps (∆ hole = 13 meV and ∆ electron = 12 meV) for quasi-two-dimensional hole and electron pockets that have similar diameters at the Γ and M points were reported by ARPES studies, 22) suggesting that the ideal nesting condition with the (π, π) wave vector referred to the tetragonal reciprocal lattice.…”
Section: -9)mentioning
confidence: 89%
See 1 more Smart Citation
“…22,23) This multiband nature implies multi-gap superconductivity in CaKFe 4 As 4 . Two superconducting gaps which are nodeless and isotropic were, indeed, observed by scanning tunneling microscopy, 20) optical conductivity, 24) penetration depth, 21) muon spin rota- * k iida@cross.or.jp tion, 18) and 75 As nuclear magnetic resonance (NMR) 25) measurements. The largest superconducting gaps (∆ hole = 13 meV and ∆ electron = 12 meV) for quasi-two-dimensional hole and electron pockets that have similar diameters at the Γ and M points were reported by ARPES studies, 22) suggesting that the ideal nesting condition with the (π, π) wave vector referred to the tetragonal reciprocal lattice.…”
Section: -9)mentioning
confidence: 89%
“…16,18) Various measurements 15,16,[18][19][20][21] indicated that CaKFe 4 As 4 shows behaviors similar to optimally or slightly overdoped (Ba 1−x K x )Fe 2 As 2 . Angle-resolved photoemission spectroscopy (ARPES) measurements supported by density functional theory calculations indicated that the Fermi surface consists of three-hole pockets at the Γ point and two electron pockets at the M point.…”
Section: -9)mentioning
confidence: 99%
“…We report inelastic light scattering results on the stoichiometric and fully ordered superconductor CaKFe 4 As 4 as a function of temperature and light polarization. In the energy range between 10 and 315 cm −1 (1.24 and 39.1 meV) we observe the particle-hole continuum above and below the superconducting transition temperature T c and seven of the eight Raman active phonons.…”
mentioning
confidence: 99%
“…CaKFe 4 As 4 is among the few iron-based compounds which are superconducting at a high transition temperature T c at stoichiometry [1] since the Ca and K atoms form alternating intact layers, as shown in Fig. 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation